2021
DOI: 10.1002/onco.13918
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Clinical and Economic Outcomes in Selected Immune-Related Adverse Events Among Patients with Cancer Receiving Immune Checkpoint Inhibitors

Abstract: Background. With increased use of immune checkpoint inhibitors (ICIs) among cancer patients, there is substantial interest in understanding clinical, economics outcomes and management of immune-related adverse events (irAEs). Patients and Methods. A retrospective study was conducted using Premier Healthcare Database, a US national hospital discharge database, from March 1, 2015 through December 31, 2017. The database comprises more than 880 million inpatient and hospital-based outpatient encounters with more t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Potential risk factors for thyroid dysfunction caused by ICIs include the presence of antithyroid antibodies at baseline, higher TSH values at baseline, and dose, duration, sex, and higher BMI values in patients receiving anti-PD-1 antibody therapy, which may be associated with a high-risk of thyroid dysfunction ( 31 , 35 ). In addition, thyroid autoantibodies may play a role in thyroid dysfunction associated with ICIs ( 36 ). Maekura et al.…”
Section: Discussionmentioning
confidence: 99%
“…Potential risk factors for thyroid dysfunction caused by ICIs include the presence of antithyroid antibodies at baseline, higher TSH values at baseline, and dose, duration, sex, and higher BMI values in patients receiving anti-PD-1 antibody therapy, which may be associated with a high-risk of thyroid dysfunction ( 31 , 35 ). In addition, thyroid autoantibodies may play a role in thyroid dysfunction associated with ICIs ( 36 ). Maekura et al.…”
Section: Discussionmentioning
confidence: 99%
“…If untreated, they lead to increased hospitalizations for management of these adverse events [ 21 ]. It has been shown that the patients requiring inpatient admission for management of irAEs have significantly higher percentage of readmission, all-cause in-hospital mortality, length of stay, and lower retention of ICI therapy [ 22 ]. This contributes significantly to healthcare-related costs.…”
Section: Discussionmentioning
confidence: 99%
“…The average total cost of medical care after a diagnosis of hypophysitis is estimated to be $16,465 whereas the average cost associated with diabetes, thyroid dysfunction, and adrenal insufficiency is $9,453, $9,399, and $3,974, respectively. The overall mean (±SD) cost was $29,477 (± $48,087) for patients with an inpatient baseline irAE-related visit and $5,718 (± $13,720) for patients with a baseline irAE-related outpatient visit [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…While oncologists, rheumatologists, and other specialists treat irAEs in outpatient clinics, some oncology clinicians and hospitalists have roles in identification and management of irAEs in inpatient settings. Additionally, irAEs that require inpatient treatment are typically of higher grade and have a higher cost burden on the healthcare system [5,6].…”
Section: Introductionmentioning
confidence: 99%